2018
DOI: 10.1080/1828051x.2018.1426397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weaning age on intestinal mucosal morphology, permeability, gene expression of tight junction proteins, cytokines and secretory IgA in Wuzhishan mini piglets

Abstract: To evaluate the effects of weaning age on intestinal mucosal morphology, expressions of tight junction proteins and inflammatory cytokines, as well as secretory IgA (sIgA) of Wuzhishan piglets, a total of 96 piglets at 1-day old with an average body weight of 0.56 ± 0.07 kg were randomly divided into four treatments with four replicates per treatment and 6 pigs per replicate. Piglets in those four treatments were weaned at the age of 21(21W), 28(28W), 35 (35W) and 42 (42W) days, respectively. Blood sample was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
1
13
1
Order By: Relevance
“…Weaning age is a controversial topic of discussion regarding performance and welfare, with typical weaning age varying between production systems and countries. Most studies agree that weaning at an early age (<21 days old) exacerbate the effect of weaning stress (Smith et al, 2010;Xun et al, 2018) but our results suggest that later weaning at 35d could also have negative impact on the piglets welfare.…”
Section: Discussionsupporting
confidence: 60%
“…Weaning age is a controversial topic of discussion regarding performance and welfare, with typical weaning age varying between production systems and countries. Most studies agree that weaning at an early age (<21 days old) exacerbate the effect of weaning stress (Smith et al, 2010;Xun et al, 2018) but our results suggest that later weaning at 35d could also have negative impact on the piglets welfare.…”
Section: Discussionsupporting
confidence: 60%
“…Wuzhishan pig is a miniature pig breed originating from Hainan Island of China. In the previous study, we found that weaning at the 35th day after birth was more beneficial to the intestinal barrier function of Wuzhishan piglets than weaning at the 21st day after birth (33). Therefore, the purpose of this study was to determine the effects of single and combined use of CUR and PIP on growth performance, intestinal barrier function, and antioxidant capacity of 35-day-old weaned Wuzhishan piglets.…”
Section: Introductionmentioning
confidence: 93%
“…The weaning age of modern pig systems has declined over time [30]. It has been reported that weaning of Wuzhishan piglets at 21 days of age old may have positive effects on the adaptive immune system [31]. Some researchers have explored the quantitative changes in the two main stem cell populations between the small intestines of 0-and 21-day-old piglets [32]; however, the difference on the physical and immunological components of small intestines between neonatal and weaned piglets remains unknown.…”
Section: Discussionmentioning
confidence: 99%